Activation of MAIT cells by antigen presenting cells: a comprehensive analysis and assessment of HIV and TB disease on these interactions - Balfour, Avuyonke (Department of Medicine, 2020)
MAIT cells are non-classical, innate-like T lymphocyte subsets, which recognize microbial vitamin B metabolites and rapidly respond by producing pro-inflammatory cytokines such as IFN-γ, TNF-α and cytotoxic molecules, which may result in the killing of bacteria-infected cells. Unlike conventional T cells, MAIT cells can be activated by either antigen presentation on MR1 or directly by cytokines. MAIT cells play a protective role against bacterial infections in mice but so far, no human studies have confirmed a direct role of MAIT cells in the control of bacterial infections or prevention of disease progression. Circulating MAIT cell numbers decrease in patients with active TB, but findings regarding functional changes have been conflicting. The aims of this study were to assess the cellular interactions between antigen presenting cells and MAIT cells, and determine the effect of TB, HIV and HIV-associated TB on MAIT cell numbers, activation, inhibitory and functional profile. We recruited 26 healthy controls (HC) without HIV or TB disease, 30 people with HIV only, 30 with active TB only, and 26 with HIV-associated TB. All TB patient samples were obtained before treatment. Blood was collected from all participants and peripheral blood mononuclear cells (PBMC) isolated from the blood and cryopreserved. Later, PBMC were thawed, rested and stimulated with BCG expressing GFP (BCG-GFP) and heat-killed (HK) M.tb. Media only, LPS and PHA were used as stimulation controls. The numbers, functional profile, inhibitory and activation status of MAIT cells were determined by flow cytometry. Soluble cytokines were measured by ELISA and multiplex Luminex assays. For HIV-infected participants with no TB and patients with HIV-associated TB, the median CD4 counts were 501 cells/µL and 228 cells/µL, and HIV viral loads were 1673 copies/mL and 66509 copies/mL, respectively. 63% and 69% of HIV infected patients were on ART in the HIV alone and HIV/TB groups, respectively. We observed lower frequencies of circulating MAIT cells in individuals with active TB only or HIV only compared to HC. HIV/TB resulted in lower but nonsignificant MAIT cell frequencies and numbers compared to HC. In response to stimulation with whole mycobacteria, MAIT cells were more highly activated (expressing high HLA-DR) in people with TB and HIV-associated TB compared to HC. Furthermore, MAIT cells from people with active TB only had significantly upregulated PD-1 expression compared to HC. MAIT cells from individuals with active TB and HIV-associated TB had a lower capacity to degranulate (express CD107a) and produce IFN-γ compared to HC. HIV-infection alone did not affect these functions. The levels of soluble IFN-α2 were reduced in the groups with HIV only and active TB only while IFN-γ was reduced in all patient groups. Blocking experiments revealed that MAIT cell activation in response to BCG was primarily through MR1 antigen presentation pathway. The level of monocyte and dendritic cell infection (expression of GFP) was similar in all groups. We observed a positive correlation between monocyte infection and the frequencies of MAIT cells producing IFN-γ in people with active TB only. We also observed a positive correlation between the amount of soluble IL-12 and the proportion of MAIT cells producing IFN-γ and CD107a in HC and in people with HIV infection, respectively. Our data show that HIV, TB and or HIV/TB result in a decrease in circulating MAIT cells, impaired functional profile, and a significant alteration in activation status and inhibitory potential. The MR1 antigen presentation was the predominant pathway for MAIT cell activation. There was also a relationship observed between MAIT cell activation and magnitude of innate response to mycobacterial antigens. These results provide further evidence of the potential role of MAIT cells in infectious disease pathogenesis and demonstrate how HIV and TB alter their function.